THE RELEVANCE OF THE SCIENCE OF JARH WA TA’DIL TO THE VALIDITY OF HADITH IN THE DIGITAL ERA - Zulfa Nur Fadhilah Zulfa (PT. Jurnal Center Indonesia Publisher, 2025)
The science of Jarh wa Ta’dil is one of the main branches in the study of Hadith Science which plays a role in assessing the moral credibility and intellectual abilities of the narrators. In classical times, this science became an important foundation in ensuring the validity of the sanad of hadith. However, amidst the rapid development of technology and the rapid flow of religious information through digital media, serious challenges have emerged in the process of verifying hadith, especially on platforms with minimal scientific studies. This study aims to examine the sustainability and application of the principles of Jarh wa Ta’dil in responding to the rampant disinformation of hadith in the digital era. Using a descriptive qualitative approach and literature study, this article concludes that the critical principles in the Science of Jarh wa Ta’dil remain relevant and can be developed to support digital religious literacy. One solution is through a digitalization system of hadith based on sanad and the authority of the narrators. The synergy between the heritage of classical science and advances in information technology is an important step in maintaining the authenticity of Islamic teachings from deviant narratives.